2013
DOI: 10.1117/12.2030274
|View full text |Cite
|
Sign up to set email alerts
|

Selected properties of multi-terminal resistors embedded in printed circuit boards

Abstract: Modern electronic devices are more and more complex and multifunctional. It could be done by producing faster and more reliable active components and increasing number of passives and interconnections' density. To form such complex devices one can embed components in substrate of printed circuit board (PCB) or build multilayer boards. The other way is to form multi-terminal passive components to spare free surface and decrease number of interconnections. Authors created three-terminal thin-film (TF) resistors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…All the measurements, advanced characterizations and analyses presented above for various passive components embedded in Printed Circuit Boards as well as other our investigations not discussed in this paper (characterization of multiterminal thin-film resistors embedded in PCBs [18], determination and comparison of transient and steady-state thermal properties of thin-film, polymer and cermet thick-film as well as LTCC resistors [19], characterization of pulse durability of thin-film and polymer thick-film embedded PCB resistors [20], determination of chosen electrical and long-term stability properties of embedded capacitors and RC filters, especially with the aid of impedance spectroscopy [21,22], electrical and long-term stability characterization of planar PCB inductors [23]) confirmed that such passives with small and medium values of resistance, capacitance or inductance exhibit basic electrical properties and long-term thermal stability level acceptable for many consumer applications. …”
Section: Discussionmentioning
confidence: 98%
“…All the measurements, advanced characterizations and analyses presented above for various passive components embedded in Printed Circuit Boards as well as other our investigations not discussed in this paper (characterization of multiterminal thin-film resistors embedded in PCBs [18], determination and comparison of transient and steady-state thermal properties of thin-film, polymer and cermet thick-film as well as LTCC resistors [19], characterization of pulse durability of thin-film and polymer thick-film embedded PCB resistors [20], determination of chosen electrical and long-term stability properties of embedded capacitors and RC filters, especially with the aid of impedance spectroscopy [21,22], electrical and long-term stability characterization of planar PCB inductors [23]) confirmed that such passives with small and medium values of resistance, capacitance or inductance exhibit basic electrical properties and long-term thermal stability level acceptable for many consumer applications. …”
Section: Discussionmentioning
confidence: 98%
“…where: t -time, t -thermal time constant, DT h_maxmaximal temperature gain (thermal constant). It was Figure 1 Images of polymer thick-film embedded resistors and illustrations of cermet/LTCC ones 10 mm 2 mm 0.5 mm 0.15 mm polymer thick-film resistors thick-film cermet/L TCC resistors established that a good fit is obtained when n is 2 or 3 (Kłossowicz et al, 2013). The sample values of obtained parameters are presented in Table I.…”
Section: Resultsmentioning
confidence: 92%
“…Referring to previous studies and literature review (Kłossowicz et al, 2013;Janke, 1992;Gó recki and Zarębski, 2010;Sofia, 1995;Janke and Pietrenko, 2000), the two formulas of thermal gradient DT(t) were determined to describe results for chosen points during heating equation ( 2) and cooling equation (3) periods:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations